PELATIHAN PEMBUATAN MASKER BERBAHAN POLYPROPELENE YANG WATER REPELENT BAGI IBU PKK DI DESA ALUE IE PUTEH KABUPATEN ACEH TAMIANG - Juliati Juliati; Sukirno Sukirno; Alpidsyah Putra; Elfrida Elfrida (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The corona virus (Covid-19) is a very dangerous virus at this time which can cause death. This corona virus has symptoms including fever, dry cough, fatigue, difficulty breathing, chest pain, and loss of the ability to speak or move. According to experts, this symptom will appear in 5-6 days, but it can also occur for 14 days after exposure to the corona virus. Therefore, efforts that can be made to help the people of Alue Ie Puteh Village in preventing exposure to the corona virus are by wearing a polypropylene mask. In addition, it can increase the role and function of universities in making masks made of polypropylene to help decide the spread of the corona virus. The method applied is a direct approach which includes location surveys, socialization, lectures and practices. This approach method is used to collect data on problems faced by the community. The lecture method is carried out by providing information to the public, to find out about the benefits of making masks made of polypropylene which are useful for protecting against exposure to the corona virus. The practical method is carried out by providing training in making masks. The results achieved were the increased understanding and skills of PKK women in Alue Ie Puteh Village regarding the manufacture of masks made from polypropylene that can prevent and prevent exposure to the corona virus.